Assessment of some toxic elements levels in Iraqi marine water - Abdulnabi, Z.A. (Mesopotamian Journal of Marine Sciences, 2022)
Two methods were used for the determination of four toxic elements (mercury, arsenic, cadmium and lead) in the Iraqi marine waters. Water samples were collected from eight stations along the Iraqi marine waters. Three stations were selected from nearby zone of the Fao city in southern of Iraq towards Khor Abdullah, these regions were considered as an important navigation line on one hand between Iraq and Iran and on the other hand between Iraq and Kuwait. The other five stations were extended between Umm Qasr port towards Khor Al-Zubair port while the last station was selected from the nearby zone for confluence zone between Khor Al-Zubair port and Shatt Al-Basra canal. All the samples were collected during low tide at depth of 10 cm from surface water. Mercury and arsenic were analyzed by ICP instrument while lead and cadmium were determined through using Atomic absorption spectroscopy (AAS). The recorded data of the total concentration for all the elements have shown the average of concentration as follows: 0.0060 mg/l, 0.0765 mg/l, 0.0518 mg/l and 0.9229 mg/l for metals mercury, arsenic, cadmium and lead respectively. Moreover, some physico-chemical properties of water were recorded in these stations